Ibn Khaldun’s theory of ‘Asabiyyah and its impact on the current Muslim community - Ismail, Nurul Fadhilah; Abdul Rahim, Adibah (David Publishing Company, 2018)
This paper seeks to study the theory of ‘asabiyyah by Ibn Khaldun, a well-known North African historiographer from 14th century. It examines Ibn Khaldun’s original thoughts on ‘asabiyyah and how he did retool it for the beneficial purposes. At the same time, the paper tries to compare the term of ‘asabiyyah as proposed by Ibn Khaldun with the interpretation made by the West in the current world. This study also will give some inputs on the implementation of Ibn Khaldun’s theory of ‘asabiyyah, and it will expose how the theory could benefit the Muslim civilization to soar as a great nation. The descriptive method has been used in this study to present the right information about Ibn Khaldun and his theory. It is hoped that this study could enhance our understanding on the term of ‘asabiyyah in its positive connotation, as the term has been recognized negatively among people today